2017
DOI: 10.1080/09540121.2017.1394966
|View full text |Cite
|
Sign up to set email alerts
|

Social and structural factors increase inconsistent condom use by sex workers’ one-time and regular clients in Northern Uganda

Abstract: While sex workers (SWs) bear the brunt of the epidemic in Uganda, there remains a dearth of empirical research on the structural drivers of HIV prevention among SWs. This study examined the drivers of inconsistent condom use by one-time and regular clients of young women SWs in Gulu, Northern Uganda. Data were drawn from the Gulu Sexual Health Study, a cross-sectional study of young SWs, aged 14 years and older (2011-2012). SWs were recruited using peer/SW-led outreach, in partnership with The AIDS Support Org… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
16
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 49 publications
2
16
0
2
Order By: Relevance
“…Few studies have examined the role of trust and intimacy in condom use between sex workers and clients. Relationship intimacy or trust has been documented as a key factor that influences condom use among sex workers and clients in Jamaica (Bailey & Figueroa, 2018 ) and Uganda (Duff et al, 2018 ). One study from Uganda found that sex workers develop a sense of trust with regular or repeat clients, which has a direct negative impact on consistent condom use (Duff et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Few studies have examined the role of trust and intimacy in condom use between sex workers and clients. Relationship intimacy or trust has been documented as a key factor that influences condom use among sex workers and clients in Jamaica (Bailey & Figueroa, 2018 ) and Uganda (Duff et al, 2018 ). One study from Uganda found that sex workers develop a sense of trust with regular or repeat clients, which has a direct negative impact on consistent condom use (Duff et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…Relationship intimacy or trust has been documented as a key factor that influences condom use among sex workers and clients in Jamaica (Bailey & Figueroa, 2018 ) and Uganda (Duff et al, 2018 ). One study from Uganda found that sex workers develop a sense of trust with regular or repeat clients, which has a direct negative impact on consistent condom use (Duff et al, 2018 ). The studies that do exist document large differences in consistent condom use rates between casual and regular clients (Duff et al, 2018 ; Matovu & Ssebadduka, 2012 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…7 Few studies considered one or more structural determinants from the heaviest or emerging HIV epidemic settings of SSA, Russia or Eastern Europe. Since 2014, a number of key studies have begun to document macro-structural factors including stigma, 22,23 migration, 24,25 and downstream products of laws and policies such as policing24, and violence 2629 on HIV outcomes and access to care among sex workers in sub-Saharan Africa, with a small handful of studies from Russia and Eastern Europe. 10 Many of the published studies have been completed across Western, Central and South Africa 1825 reinforcing the consistency of significance of these relationships using a combination of quantitative and qualitative methods.…”
Section: Programmatic and Scientific Advancesmentioning
confidence: 99%
“…Engaging with the police, whether threats (e.g., verbal harassment) or actions (e.g., arrest, sexual violence) is a number of harmful outcomes. (16,33,49) In the current study, the impact of police was re ected in the signi cant association between client inconsistent condom use with both avoiding carrying condoms and moving to unfamiliar areas in all three adjusted models, both attributed to the police. An earlier study of FSW in Baltimore found associations between abusive policing practices and client-perpetrated violence, which, in turn, has been found to increase risk for inconsistent condom use.…”
Section: Discussionmentioning
confidence: 53%